Model Kebijakan Hukum Tanggung Jawab Sosial Perusahaan di Indonesia - Sefriani Sefriani; Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2017)
This research is to study the model of legal policy of CSR in Indonesia to be effectively and beneficially implemented for the companies, community and environments. This is a normative research using the statue approach, historical approach and comparative approach. The data obtained from the research were grouped in accordance with each variable to later on be analyzed qualitatively and presented in the analytical descriptive form. The result of the research showed that the model of legal policy of CSR in Indonesia is mandatory supported by the proper sanction. Any change of paradigm of Human Right also seeing the company as the one responsible for the ecosob is a strong supporting factor for the legal policy of CSR in Indonesia.